The Influence of Compensation and Work Motivation on Employee Performance - Hidayatullah, Muhammad Faris; Muhtadin, Imam (Almana : Jurnal Manajemen dan Bisnis, 2025)
In this era of globalization, every company is trying to show its superiority in order to survive in increasingly tight business competition. Companies are required to increase effectiveness and efficiency optimally so that the company's goals can be achieved. Every company has targets and goals to accomplish in a certain period. PT. Infinit Teknika Industri is a relatively new company in the industrial landscape in Indonesia. Founded in 2022 and based in Tangerang, we have established ourselves as a major player in the electrical and mechanical fields. Initially, we focused on providing high-quality electrical and mechanical equipment. However, as time passes, we realize the importance of providing a more comprehensive service. Therefore, we started offering installation services to ensure that the solutions we provide deliver optimal results for customers, with a vision to become an active contributor to national infrastructure development. The purpose of this research is to determine the influence of compensation and work motivation on employee performance. This research uses observation and questionnaire methods as instruments. The respondents were 45 employees at PT. Infinit Teknika Industri. The sampling process uses technical non-probability sampling using an associative quantitative approach using primary data. Associative quantitative data analysis technique using primary data.